Monocyte–macrophage polarization and recruitment pathways in the tumour microenvironment of B‐cell acute lymphoblastic leukaemia. (13th March 2021) - Dander, Erica; Fallati, Alessandra; Gulić, Tamara; Pagni, Fabio; Gaspari, Stefania; Silvestri, Daniela; Cricrì, Giulia; Bedini, Gloria; Portale, Federica; Buracchi, Chiara; Starace, Rita; Pasqualini, Fabio; et al.
Summary: B‐cell acute lymphoblastic leukaemia (B‐ALL) reprograms the surrounding bone marrow (BM) stroma to create a leukaemia‐supportive niche. To elucidate the contribution of immune cells to the leukaemic microenvironment, we investigated the involvement of monocyte/macrophage compartments, as well as several recruitment pathways in B‐ALL development. Immunohistochemistry analyses showed that CD68‐expressing macrophages were increased in leukaemic BM biopsies, compared to controls and predominantly expressed the M2‐like markers CD163 and CD206. Furthermore, the "non‐classical" CD14 + CD16 ++ monocyte subset, expressing high CX3CR1 levels, was significantly increased in B‐ALL patients' peripheral blood. CX3CL1 was shown to be significantly upregulated in leukaemic BM plasma, thus providing an altered migratory pathway possibly guiding NC monocyte recruitment into the BM. Additionally, the monocyte/macrophage chemoattractant chemokine ligand 2 (CCL2) strongly increased in leukaemic BM plasma, possibly because of the interaction of leukaemic cells with mesenchymal stromal cells and vascular cells and due to a stimulatory effect of leukaemia‐related inflammatory mediators. C5a, a macrophage chemoattractant and M2‐polarizing factor, further appeared to be upregulated in the leukaemic BM, possibly as an effect of PTX3 decrease, that could unleash complement cascade activation. Overall, deregulated monocyte/macrophage compartments are part of the extensive BM microenvironment remodelling at B‐ALL diagnosis and could represent valuable targets for novel treatments to be coupled with classical chemotherapy.